CORRELATION BETWEEN INTERPERSONAL INTELLIGENCE AND LEARNING MOTIVATION TO FIFTH GRADE STUDENTS OF PUBLIC ELEMENTARY SCHOOLS IN KEBUMEN SUB-DISTRICT IN ACADEMIC YEAR OF 2020/2021 - Neni Dewi Anggraeni; Rokhmaniyah Rokhmaniyah; Suhartono Suhartono (Universitas Sebelas Maret, 2021)
Learning is a need. Learning factors consist of intrinsic and extrinsic. Interpersonal intelligence and learning motivation are part of intrinsic factors. The study aimed to analyze and measure the contribution of interpersonal intelligence and learning motivation to fifth grade students of public elementary schools in Kebumen Sub-district in academic year of 2020/2021. It was correlational quantitative method. The samples were 329 fifth grade students in twelve public elementary schools throughout the Kebumen Sub-district. Sampling method was cluster sampling. Data analysis used simple correlation test (significance level of 5%) and the determinant coefficient with the help of SPSS 21 Version. The results indicated that there is a positive correlation between interpersonal intelligence. It was strong correlation (r count 0.618 > r table 0.18) and significance was 0.000<0.05. The determinant coefficient was 38%, it meant Interpersonal intelligence contributed 38% on learning motivation and the remaining 62% was influenced by other factors.